Interaksi Energetik Guru dan Siswa pada Pembelajaran Abad 21 - Ady Ferdian Noor; Muhammad Nur Wangid (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
Learning requires harmonious interaction between teachers and students. Communication is a type of action that occurs when two or more objects influence or have an effect on each other. Learning through less dynamic interactions can cause an imbalance in the transfer of learning. Tendencies that arise are students will know a lot about something, but become less have a system of values, attitudes, interests and positive appreciation of what is known. Children will experience intellectual development unbalanced by personality maturity, giving birth to a specialist figure who is less concerned with the surrounding environment and prone to value distortions. Students will practice violations such as happy fighting with friends, lack of respect for others, and lack of courtesy. The academic atmosphere in elementary schools for students to be able to learn effectively is a condition where students can collaborate, cooperate, communicate using any direction there is no fear and feel even protected, and they think treated reasonably regardless of ethnicity, religion, race, class, and gender so as to achieve desired goals both national education goals and primary school goals. Energetic interactions between teachers and students in schools must be based on functional relationships first between the teacher and students, meaning students feel the teacher is a parent and a friend who can be invited to interact without fear but still respect. Fearless but respectful interaction is needed because it fits with one of the 21st-century learning skills, collaboration. Good collaboration causes learning to be fun, so learning becomes effective.